Investigation and characterization of hardening of AISI 4140 steel using Nd:YAG laser - (:unkn) unknown (International OCSCO World Press, 2014)
Purpose: In this research, our aim was to propose an alternative to the conventional hardening methods, laser spot welding, thus laser hardening through the solid state reaction.Design/methodology/approach: Instead of diode lasers, the Neodymium:YAG Laser was used by applying different voltage, time and depths of laser and the parameters of hardening and the differences induced in the hardness’s of the specimens were investigated.Findings: The hardness of the specimens depending on the depths laser, from the edge to the deep of the specimens were measured. The metallographic examination (transformation due to the heating-cooling cycles) and the SEM analysis was made to complete the characterization.Research limitations/implications: Using Nd:YAG laser, the hardening process was easy to operate offering several advantages such as possibility of working in very small and narrow areas altering the voltage and depths of laser facilely and obtaining high hardness values due to transformation of microstructure without need of secondary quenchant.Originality/value: In this work, an alternative to the conventional hardening methods, laser spot welding was applied to AISI 4140 steel surface, which is widely used in the industry, thus laser hardening through the solid state reaction was achieved. © International OCSCO World Press. All rights reserved.
Keywords: AISI 4140 hardness; Laser spot hardening; Laser spot welding; Mechanical properties; Surface treatment